VIOLATIONS OF THE LAW IN DIGITAL COMMUNICATION ON INDONESIAN SOCIAL MEDIA - Noer Mawaddah Ainina; Supian (Adisam Publisher, 2026)
The development of social media has expanded the communication space for Indonesian people, but at the same time has increased the risk of breaking the law in digital communication. This study aims to analyze the forms of legal violations in digital communication on social media in Indonesia, the factors that cause them, the problems in implementing regulations, and strategies for their prevention. The research uses a literature review method with qualitative, descriptive, and normative juridical approaches. Data was obtained from laws and regulations, Scopus-indexed journal articles, scientific books, court decisions, and reports from official institutions relevant to digital communication and social media law. Data were analyzed using content and thematic analyses by grouping the literature according to the form of violation, causative factors, impact, and handling mechanisms. The results of the study show that violations of the law in digital communication include defamation, insults, hate speech, the spread of false information, cyberbullying, digital threats, and the dissemination of personal data without consent. These violations are influenced by low levels of legal and digital literacy, weak emotional control, user anonymity, social conflicts, and the nature of social media, which accelerates the dissemination of information. The application of the law still faces difficulties in distinguishing between criticism, opinion, satire, public interest, insults, and hate speech. This study concludes that the handling of digital communication violations must be carried out in a contextual manner, taking into account the content of the message, the communicator's intention, the target, the extent of spread, the public interest, and the impact on the victim. Prevention needs to be done through strengthening digital literacy, platform moderation, mediation, victim recovery, and the proportionate application of criminal law as a last resort.